2004
DOI: 10.1002/gcc.10321
|View full text |Cite
|
Sign up to set email alerts
|

Germ‐line mutations in BRCA1 or BRCA2 in the normal breast are associated with altered expression of estrogen‐responsive proteins and the predominance of progesterone receptor A

Abstract: The breast cancer susceptibility genes BRCA1 and BRCA2 are responsible for a large proportion of familial breast and ovarian cancer, yet little is known of how disruptions in the functions of the proteins these genes encode increased cancer risk preferentially in hormone-dependent tissue. There is no information on whether a germ-line mutation in BRCA1 or BRCA2 causes disruptions in hormone-signaling pathways in the normal breast. In this study markers of hormone responsiveness were measured in prophylacticall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
40
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(52 citation statements)
references
References 51 publications
(62 reference statements)
9
40
1
Order By: Relevance
“…biological phenotype associated with heterozygous mutations in the BRCA1 and BRCA2 genes, and complements the recent reports of an effect on PgR expression by Mote et al (2004). The delayed PgR response to E 2 in the mutation carriers is paradoxical in the face of the in vitro evidence suggesting that the BRCA1 gene product is a repressor of both nuclear and nongenomic mechanisms of ERa action (Fan et al, 1999(Fan et al, , 2001Razandi et al, 2004).…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…biological phenotype associated with heterozygous mutations in the BRCA1 and BRCA2 genes, and complements the recent reports of an effect on PgR expression by Mote et al (2004). The delayed PgR response to E 2 in the mutation carriers is paradoxical in the face of the in vitro evidence suggesting that the BRCA1 gene product is a repressor of both nuclear and nongenomic mechanisms of ERa action (Fan et al, 1999(Fan et al, , 2001Razandi et al, 2004).…”
Section: Discussionsupporting
confidence: 79%
“…One way of confirming this would be to use more specific antibodies to determine the ratios of the two PgR isoforms in the breast epithelium from the mutation carriers compared to those from subjects at population risk of breast cancer. This approach has been used by Mote et al (2004) who have shown that not only is the ratio of PgRA to PgRB altered in favour of PgRA in normal breast tissue taken from BRCA1 and BRCA2 mutation carriers but also that expression of both isoforms is markedly reduced compared to tissue from normal-risk women. This suggests that the reduced levels of PgR expression seen in the mutation carriers in the present study is due to a reduction in both PgR isoforms.…”
Section: Discussionmentioning
confidence: 99%
“…In humans, loss of function of one BRCA1 allele has been associated with a relative increase in PR A levels, alterations in ERa-regulated gene expression, but a normal ERa expression pattern (Mote et al, 2004). Similarly, in the study reported here, a normal pattern of nuclear-localized ERa expression was found in the normal-appearing mammary ductal cells.…”
Section: Discussionsupporting
confidence: 74%
“…In vitro studies indicate that PgR-A exerts modulating effects on cell morphology and adhesion (McGowan et al 1999;Grahal et al 2005). In the normal tissue of BRCA mutation carriers, PgR-B is absent (Mote et al 2004). …”
Section: Progesterone Receptors (Pgr)mentioning
confidence: 99%